Role of Sonographic Diagnosis in Managing Bethesda Class III Nodules - Kim, D.W.; Lee, E.J.; Jung, S.J.; Ryu, J.H.; Kim, Y.M. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Bethesda class III cytology is an important limitation of the US-FNA in assessing thyroid nodules. This study aimed to assess the diagnostic efficacy of US in evaluating thyroid nodules with Bethesda class III cytology. MATERIALS AND METHODS: From January 2008 to December 2009, 1036 patients with 1289 thyroid nodules diagnosed by US and subsequent US-FNA biopsy were enrolled in the study. On the basis of US features, each thyroid nodule was prospectively classified by a single radiologist into 1 of 5 diagnostic categories: benign, probably benign, borderline, possibly malignant, and malignant. Solid nodules were classified by using all 5 categories, whereas partially cystic nodules were classified by using 4 (borderline was omitted). We calculated the diagnostic efficacy of thyroid US by comparing the US diagnoses with the histopathology results of Bethesda class III nodules. RESULTS: Of the 51 Bethesda class III nodules, 35 were surgically confirmed and 8 were histologically diagnosed, and a malignancy rate of 46.5% (20/43) was determined. From the 43 nodules, the sensitivity, specificity, positive and negative predictive values, and accuracy were calculated with 9 borderline nodules excluded (100%, 94.7%, 93.3%, 100%, and 97.0%, respectively) and with the 9 when reclassified as benign (63.6%, 95.2%, 93.3%, 71.4%, and 79.1%, respectively) and malignant (100%, 85.7%, 88.0%, 100%, and 93.0%, respectively). The values obtained with exclusion and malignancy reclassification of 9 borderline nodules were not significantly different (P = .250). CONCLUSIONS: US diagnosis by using the present US classification system can be helpful for managing Bethesda class III nodules. CNBcore-needle biopsyFNAfine-needle aspirationPCTNpartially cystic thyroid noduleUSsonography